IMPLEMENTASI ASAS KEHATI-HATIAN DALAM PERLINDUNGAN DATA PRIBADI BERDASARKAN UNDANG-UNDANG NOMOR 27 TAHUN 2022 TENTANG PERLINDUNGAN DATA PRIBADI DI ERA DIGITAL 5.0 - Andri Pranata; Agustinus Arif Juono, Binarida, Aullia Vivi Yulianigrum (INTELIGENSIA MEDIA, 2024)
In the digital era, personal data protection has become a crucial aspect to maintain social stability and public trust. This article examines the implementation of the principle of caution in personal data protection in Indonesia based on Law Number 27 of 2022 concerning Personal Data Protection. This research uses a normative method with a conceptual and legislative approach, supported by descriptive- qualitative analysis. The results show that despite the regulations being implemented, there are still several obstacles such as lack of understanding, technological limitations, high costs, shortage of experts, and suboptimal coordination between institutions. To overcome these obstacles, efforts are needed to increase education and socialization, invest in security technology, train experts, and enhance coordination between related institutions. Thus, personal data protection in Indonesia can be more effective in facing the challenges of the digital era.